THE EFFECT OF CHARACTERISTICS OF MANAGEMENT ACCOUNTING SYSTEM INFORMATION (BROADSCOPE, TIMELINESS, AGGREGATION, AND INTEGRATION) AND DECENTRALIZATION OF MANAGERIAL PERFORMANCE - Sari, Intan Purnama; Noviana, Melody (Universitas Brawijaya, Indonesia, 2022)
This study tested the hypothesis developed by Chenhall and Morris (1986) and aims to examine the effect of management information system characteristics of management accounting and decentralization on managerial performance. This study uses contingency theory as a grand theory because the theory of the contingency approach is based on the premise that no management accounting system is always appropriate for all types of companies. This study was analyzed using multiple linear regression analysis. This study used a survey method using a questionnaire with 41 respondents consisting of 5 area managers and 36 supervisors at one pharmaceutical company in Bali province. The results showed that the characteristics of management accounting system information in broadscope, timeliness, aggregation, and integration did not affect managerial performance. It is because managers and supervisors do not fully use the information of the existing management accounting system, so the information management accounting system does not contribute to decision-making that will impact managerial performance. The results of this study are not in line with previous research, but this research supports the contingency theory approach. The decentralization variable has a significant effect on managerial performance. These results support previous research showing that delegating authority from officials to lower-level officials can assist management in making decisions better to improve managerial performance.